Contribution on water transportation for resilient and sustainable lowland cities - P. Iamtrakul; I. Raungratanaamporn; J. Klaylee (Lowland Technology International, 2018)
Due to a force for development has resulted to rapid urbanization in Bangkok and its vicinities. The attractions of megacity create high number of jobs and opportunities, consequently accessibility and mobility has become super congested which has long been called for sustainable solution to tackle with this problematic of urbanization. A need to change the current supply leads to urgent need of an alternative mode choice for commuters, and adopt a new paradigm of mobilization where suburban urbanization evolves in Bangkokians’ daily life. This study aimed to provide an unconventional solution to meet the current mobility needs through the introduction of water transport systems that focus on access, safety and efficiency within the larger context of reducing commuting time in Bangkok urban areas. This effort through its various initiatives to return the role of Bangkok canal network in more sustainable option include the business model option along with social engagement of community people to own their water transport. Finally, this contribution could then help Bangkok not only towards urban mobilizing, but also for resilient and sustainable lowland cities under the risk of flooding in term of mitigation and management.